A Network-Guided Approach to Discover Phytochemical-Based Anticancer Therapy: Targeting MARK4 for Hepatocellular Carcinoma - Ahmed, Sarfraz; Mobashir, Mohammad; Al-Keridis, Lamya Ahmed; Alshammari, Nawaf; Adnan, Mohd; Abid, Mohammad; Hassan, Md Imtaiyaz (Frontiers in Oncology, 2022)
MAP/microtubule affinity-regulating kinase 4 (MARK4) is associated with various biological functions, such as neuronal migration, cell polarity, microtubule dynamics, apoptosis, and cell cycle regulation, specifically in the G1/S checkpoint, cell signaling, and differentiation. It plays a critical role in different types of cancers. Hepatocellular carcinoma (HCC) is the most common forms of liver cancer caused due to mutations, epigenetic aberrations, and altered gene expression patterns. Here, we have applied an integrated network biology approach to see the potential links of MARK4 in HCC and subsequently identified potential herbal drugs. This work potentially focuses on the naturally-derived compounds from medicinal plants and their properties, making them targets for potential anti-hepatocellular treatments. Moreover, we have also analyzed the HCC mutated genes from the TCGA database by using cBioPortal and mapped out the MARK4 targets among the mutated list. We screened potential plant products, identified critically altered genes followed by their pathways, and predicted the putative potential drug targets by considering the complexity associated with this cancer and therapeutic potentials. MARK4 and Mimosin, Quercetin, and Resveratrol could potentially interact with critical cancer-associated proteins. A set of the hepatocellular carcinoma altered genes is directly the part of infection, inflammation, immune systems, and cancer pathways. Finally, we conclude that among all these drugs, Gingerol and Fisetin appear to be the highly promising drugs against MARK4-based targets, followed by Quercetin, Resveratrol, and Apigenin.